How paediatric nursing can leverage the age of artificial intelligence to improve health outcomes and quality of care? - Pranay Bende (Wiley, 2024)
Abstract The comprehensive holistic care for paediatric patients is essential but artificial intelligence is playing a vital role where accuracy with limited duration a constructive health care services can be delivered to the children where indirectly nurses are getting technically skilled and more developed then the previous nursing services.